ANALISIS PENERAPAN e-SPT PPN TERHADAP KEPATUHAN WAJIB PAJAK - Dini Wahyu Hapsari (Universitas Trunojoyo Madura, 2014)
The objective of this research is to investigate the effect of the utilization of tax computerized system with Electronic Value-added Tax Form on tax payers compliance. The research method used is associative method with survey approach. The analysis technique used to test the effect among variables are validity and reliability test, Spearman Rank Correlation Coefficient test, regression test, and t-Test for hypothesis. The analysis shows that Spearman Rank coefficient calculation results in 0,646 which is between 0,60 and 0,80. This number suggests that there is “strong” interpretation relationship. On the other hand, the determination coefficient calculation suggests that the contribution of variable of computerized-tax system with electronic-form of Value-added Tax to the tax payer compliance is 41,7%; where the rest 58,3% is affected by other factors. The regression equation gathered is Y’ = 33.256 + 0,598 X which shows positive effect, means every increasing of one unit of variable of computerized-tax system with electronic-form of Value-added Tax, the tax payer compliance will increase for 0,598 unit. While for hypothesis testing, it can be concluded that there is significant effect of the utilization of tax computerized system with Electronic Value-added Tax Form on tax payers compliance.